Komparasi Tata Kelola Pariwisata di Kabupaten Tanggamus (Studi pada Destinasi Wisata Air Terjun Way Lalaan dan Bukit Idaman) - Saputri, Diana; Kagungan, Dian; Faedlulloh, Dodi (Administrativa : Jurnal Birokrasi, Kebijakan dan Pelayanan Publik, 2025)
The issueiof tourismigovernance in touristiattractions in Tanggamus Regency still needsimore attention. Soithat improvementsiand additional insightsiare needed for tourist attraction managers in organizing and managing tourist attractions. There are severalitourist attractions iniTanggamus Regencyithat areimanaged by the governmentiand privateisuch as theiWay Lalaan Waterfall tourist attraction managed by the Tourism Office and the Bukit Idamanitourist attraction managed by the private sector. Good governance can be measured through several factors namely, Positive culture Constructive communication and engaged communities, transparency and accountability, vision and leadership, acceptance in diversity (tolerance), developing knowledge, learning and sharing expertise, clear participant roles and responsibilities, clear operational structures and out-of-network processes This study aims to describe and analyze how tourism governance in two tourist attractions, namely Way Lalaan Waterfall and Bukit Idaman tourist attraction in Tanggamus Regency by comparing governance in two tourist attractions. The method used is a descriptive qualitative research method from data collection with interviews, observations, and documentation. The results of this study after comparing the two governances of the two tourist attractions were found that the results of tourism governance at the Way Lalaan Waterfall tourist attraction were better than the Bukit Idaman tourist attraction by referring to the 7 indicators used in this study. This is supported by stakeholders in the governance of the Way Lalaan Waterfall tourist attraction which is very complex because it consists of local governments, the private sector and also community elements. However, there is a shortcoming in one indicator in the tourism governance of Way Lalaan Waterfall, which is Transparent and accountable, namely in terms of budgeting funds must pass through many stakeholders.